Removal of Cr(VI) and Cu(II) Ions from Aqueous Solution by Carbon Prepared from Henna Leaves - T. Shanthi; V. M. Selvarajan (Journal of Chemistry)
Carbon prepared from leaves of henna (Lawsonia inermis) was used to study the adsorption of Cr(VI) and Cu(II) ions from their aqueous solutions. The experimental conditions which include pH, contact time, initial concentration, and adsorbent dosage on the metal removal were investigated. The capacity of adsorption depends on pH value; it increases with an increase in pH value from 1 to 7 and then decreases. The highest percentage of metal removal was achieved in the adsorbent dosage of 0.7 g and at an initial concentration of 100 ppm metal ion. The adsorption isotherm studies revealed that data was confirmed with both the Langmuir and Freundlich isotherm models. The removal percentage was found to be higher for Cu(II) when compared with Cr(VI). The potential of carbon prepared from henna leaves for the removal of these two solutions containing heavy metals was substantiated.